Are the treasures of game theory ambiguous? - Eichberger, Jürgen; Kelsey, David (Economic theory, 2011)
Goeree and Holt (Am Econ Rev 91:1402-1422, 2001) experimentally study a number of games. In each case, they initially find strong support for Nash equilibrium; however, by changing an apparently irrelevant parameter, they find results which contradict Nash equilibrium. In this paper, we study the five normal form games from Goeree and Holt (Am Econ Rev 91:1402-1422, 2001). We argue that their results may be explained by the hypothesis that subjects view their opponents’ behaviour as ambiguous. Ambiguity-aversion causes players to avoid strategies, which give low out of equilibrium payoffs. Similarly, ambiguity preference can make strategies with high payoffs more attractive.
Gesehen am 11.04.2022